The effect of maturity and crop load on the browning and concentration of phenolic compounds of Thompson Seedless and Regal Seedless - Kamfer, De Witt (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2014.